Gray and white matter volume abnormalities in generalized anxiety disorder by categorical and dimensional characterization. Issue 3 (30th December 2015) - Hilbert, Kevin; Pine, Daniel S.; Muehlhan, Markus; Lueken, Ulrike; Steudte-Schmiedgen, Susann; Beesdo-Baum, Katja
Abstract: Increasing efforts have been made to investigate the underlying pathophysiology of generalized anxiety disorder (GAD), but only limited consistent information is available on gray (GM) and white matter (WM) volume changes in affected adults. Additionally, few studies employed dimensional approaches to GAD pathology. This study compares structural brain imaging data from n =19 GAD subjects and n =24 healthy comparison (HC) subjects, all medication-free and matched on age, sex and education. Separate categorical and dimensional models were employed using voxel-based morphometry for GM and WM. Significantly higher GM volumes were found in GAD subjects mainly in basal ganglia structures and less consistently in the superior temporal pole. For WM, GAD subjects showed significantly lower volumes in the dlPFC. Largely consistent findings in dimensional and categorical models point toward these structural alterations being reliable and of importance for GAD. While lower volume in the dlPFC could reflect impaired emotional processing and control over worry in GAD, basal ganglia alterations may be linked to disturbed gain and loss anticipation as implicated in previous functional GAD studies. As perturbations in anticipation processes are central to GAD, these areas may warrant greater attention in future studies. Highlights: Generalized Anxiety Disorder pathology was investigated. Categorical and dimensional voxel-based morphometry approaches were used. Volume alterations were found in the dorsolateral prefrontal cortex and basal ganglia. Changes may reflect impaired emotional processing and anticipation processes. Main results were comparable for both approaches.